Emissions Trading: Impact on Electricity Prices and Energy-Intensive Industries - Manuel Frondel; Christoph M. Schmidt; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
The EU-wide Emission Trading Scheme (ETS), established in 2005, is a key pillar of Europes strategy to attain compliance with the Kyoto Protocol. Under this scheme, CO2 allowances have thus far been allocated largely free of charge. This paper demonstrates that such cost-free allocation, commonly called grandfathering, implies an increase in electricity prices even when strong competition prevails on electricity markets. As our estimations for Germanys power sector show, these price increases result in substantial windfall profits, giving rise to public skepticism and calls for an auctioning of certificates in the future. While empirical evidence on the ETS impacts is scant, the findings reviewed here indicate that even in the absence of certificate auctioning, energy-intensive industry sectors, such as primary aluminum production, may suffer heavily from the ETS-induced electricity price increases. We therefore argue that an abrupt transition to a complete auctioning system may endanger the competitive position of energy-intensive industries in Europe, unless all other major industrial and transition countries are integrated into a global emissions trading system.
Keywords: Q41; Q48; 330; Grandfathering; auctioning; competition; Emissionshandel; Kohlendioxid; Allokation; Auktion; Wirtschaftspolitische Wirkungsanalyse; Stromtarif; Windfall Profit; Elektrizitätswirtschaft; Industrie; Energiekonsum; Internationaler Wettbewerb; EU-Staaten